an object is thrown in vertical upward direction with velocity‘ u ’then the maximum height attained main object would be......... .
Answers
Given :
- The velocity with which the object is thrown in vertical upward direction is 'u'
To find :
- The Maximum height attained by the object
Solution :
When a body/object is thrown vertically upwards the velocity(final velocity) at highest point will be zero.
And the acceleration experienced by the object/body is nothing but the acceleration due to gravity which is equal to -g. (Negative sign indicates that the acceleration is opposite direction of motion)
Initial velocity of the object/body is the velocity with which it is thrown . So , In this case initial velocity of the object will be 'u'.
Now we have ,
- u = u
- v = 0
- a = -g
- s = h (height attained in this case)
From Second equation of motion ,
Where ,
- v is Final velocity
- u is initial velocity
- a is acceleration
- s is height attained (in this case)
Substituting the values we have ,
Hence , The Maximum height attained by the object is
Answer:
Given :
The velocity with which the object is thrown in vertical upward direction is 'u'
To find :
The Maximum height attained by the object
Solution :
When a body/object is thrown vertically upwards the velocity(final velocity) at highest point will be zero.
And the acceleration experienced by the object/body is nothing but the acceleration due to gravity which is equal to -g. (Negative sign indicates that the acceleration is opposite direction of motion)
Initial velocity of the object/body is the velocity with which it is thrown . So , In this case initial velocity of the object will be 'u'.
Now we have ,
u = u
v = 0
a = -g
s = h (height attained in this case)
From Second equation of motion ,
\star \: { \boxed{ \sf{ \purple{v {}^{2} - u {}^{2} = 2as }}}}⋆
v
2
−u
2
=2as
Where ,
v is Final velocity
u is initial velocity
a is acceleration
s is height attained (in this case)
Substituting the values we have ,
\begin{gathered}: \implies \sf \: (0) {}^{2} - (u) {}^{2} = 2( - g)(h) \\ \\ : \implies \sf \: 0 - u {}^{2} = - 2gh \\ \\ : \implies \sf \: - u {}^{2} = - 2gh \\ \\ : \implies \sf \not{ - }u {}^{2} = \not{ - }2gh \\ \\ : \implies \sf \: {u}^{2} = 2gh \\ \\ : \implies {\boxed{ \sf {\pink {\: h = \frac{ {u}^{2} }{2g} }}}}\end{gathered}
:⟹(0)
2
−(u)
2
=2(−g)(h)
:⟹0−u
2
=−2gh
:⟹−u
2
=−2gh
:⟹
−u
2
=
−2gh
:⟹u
2
=2gh
:⟹
h=
2g
u
2
Hence , The Maximum height attained by the object is \sf{\dfrac{u^2}{2g}}
2g
u
2